SIGIMA (Sistem Informasi Sehat Jiwa Remaja): Upaya Deteksi Dini Kesehatan Mental Berbasis Digital pada Remaja - Liyanovitasari; Puji Lestari; Zumrotul Chairiyyah; Yoannes Romando Sipayung (UNIVERSITAS NGUDI WALUYO, 2026)
School-age adolescents, particularly those in vocational high schools (SMK), face complex psychosocial challenges. These challenges include the demands of the academic curriculum, identity crises, peer group dynamics, and anxiety in the transition to the workforce or higher education. Therefore, a preventive, proactive, and relevant intervention is needed through the use of digital technology